The 4th industrial revolution and its impact on entrepreneurial education - Culduz, Murat (IGI Global, 2024)
The 4th Industrial Revolution is transforming the way that businesses operate and has had a profound impact on the field of entrepreneurial education. With the rapid pace of technological change and innovation, entrepreneurs need to be equipped with a diverse range of skills and competencies to succeed. This includes digital literacy, which is essential for navigating the digital landscape of the 4th Industrial Revolution, as well as an entrepreneurial mindset, which emphasizes creativity, innovation, risk-taking, and adaptability. Interdisciplinary knowledge is also becoming increasingly important, as entrepreneurs must be able to understand the complex interplay between technology, business, and society. Additionally, collaborative, and experiential learning can help entrepreneurs to develop practical skills, build networks, and gain real-world experience. In this context, the aim of the study is to is to shed light on the 4th Industrial Revolution and its impact on entrepreneurial education benefiting from the recent studies in the literature.
Keywords: Entrepreneurship Education; University Students; Self-Efficacy